Fractured politics? The comparative regulation of shale gas in Europe. Issue 9 (2nd September 2018) - Van de Graaf, Thijs; Haesebrouck, Tim; Debaere, Peter
ABSTRACT: European countries have developed strikingly different responses to shale gas and fracking. Some have imposed outright bans, while others have issued permits and even awarded generous tax breaks to the industry. To explain this puzzling variance, this article builds a theoretical framework that focuses on energy security, economic competitiveness, the party composition of government, public opinion, multilevel governance and democratic tradition. It then conducts a qualitative comparative analysis (QCA) of the regulation of shale gas in 16 European Union member countries. We find that the level of public concern is a sufficient condition for restrictive regulation. Other conditions only work in combination with others, while energy security and democratic tradition have no impact on the regulation of shale gas and fracking. The findings indicate that the uptake of shale gas is not simply a function of structural factors such as geology or population density, but rather the result of political factors.